Methane production by mechanochemical processing of MgH2-Li2CO3 as sources of H2 and CO2 at room temperature. Issue 40 (September 2020) - Grasso, María L.; Fernández Albanesi, Luisa; Garroni, Sebastiano; Mulas, Gabriele; Gennari, Fabiana C.
Graphical abstract: Highlights: CH4 /H2 fuel mixture is obtained by mechanical milling of MgH2 -Li2 CO3 at room temperature. Mechanochemical process occurs without catalyst and with high selectivity to methane. Analyses of the gas-product evolution evidences the absence of CO2 or CO during milling. Methane generation is kinetically restricted by the high stability of Li2 CO3 . Solid products are reused as CO2 absorbers for the exhaust gases treatment of power plants. Abstract: The reutilization of CO2 to produce valuable chemical fuels is an attractive approach to reduce the greenhouse effect and global warming. In this work, the room temperature production of CH4 /H2 fuel mixtures via mechanochemical activation of Li2 CO3 -MgH2 system was explored. The CH4 /H2 fuel mixtures were obtained by a free-catalyst reaction, with high selectivity and using Li2 CO3 and MgH2 as solid portable sources of CO2 and H2, respectively. The effect of processing parameters on both the evolution of the solid phases and the production of CH4 /H2 fuel mixtures was studied using X-ray diffraction, spectroscopic techniques, electron scanning microscopy and gas chromatography. Thermodynamic calculations predict the complete CO2 reduction to CH4, with simultaneous formation of MgO and Li2 O. Experimental evidence supports the progressive formation of MgO and the appearance of Li2 O. The presence of H2 simultaneously with CH4 in the gas phase was due to kinetic restrictions. Based on experimental results and equilibrium composition calculations, the reaction mechanism was proposed. The kinetic analysis reveals that the rate limiting CH4 production is the nucleation of MgO/Li2 O in the surroundings of Li2 CO3, while the H2 release is controlled by the reaction interface between MgH2 /Mg or MgH2 /MgO.